Tanggung Jawab Hukum Penggunaan Artificial Intelligence Terhadap Pelanggaran Data Pribadi Pada Platform E-Commerce - Putra, Agitkarai Sirajuddin; Lalu Muh. Hayyanul Haq (Commerce Law, 2024)
The issue of data privacy is central in today’s digital environment, especially in the e-commerce sector, which uses AI technology. Data privacy breaches can impact users, e-commerce businesses, and society. This research aims to determine the impact of artificial intelligence in e-commerce platforms on consumer personal data. Until now, Indonesian law has not had regulations that specifically regulate AI. However, based on Article 1, number 8 of the ITE Law and Article 1, number 3 of PP PSTE in Indonesia, AI can be equated with an Electronic Agent. In its implementation, the E-Commerce platform that uses AI has implemented regulations governing the protection of personal data, namely PDP Law Number 27 of 2022, ITE Law Number 19 of 2016, PP PSTE No. 71 of 2019, and Regulation of the Minister of Communication and Information of the Republic of Indonesia No. 20 of 2016 concerning Protection of Personal Data in Electronic Systems.